Estimation of carbon dioxide (CO2) reduction by utilization of algal biomass bioplastic in Malaysia using carbon emission pinch analysis (CEPA) - Abdul-Latif N.-I.S.; Ong M.Y.; Nomanbhay S.; Salman B.; Show P.L. (Taylor and Francis Inc., 2023)
carbon; carbon dioxide; phenol; plastic; biofuel; carbon dioxide; Article; biomass; carbon footprint; crop; greenhouse; macroalga; Malaysia; microalga; nonhuman; pyrolysis; reduction (chemistry); seaweed; biomass; environmental monitoring; growth, development and aging; metabolism; Biofuels; Biomass; Carbon Dioxide; Environmental Monitoring; Malaysia; Seaweed